2011
DOI: 10.1371/journal.pone.0017145
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Modifications of Neisseria meningitidis after an Accidental Human Passage

Abstract: A scientist in our laboratory was accidentally infected while working with Z5463, a Neisseria meningitidis serogroup A strain. She developed severe symptoms (fever, meningism, purpuric lesions) that fortunately evolved with antibiotic treatment to complete recovery. Pulse-field gel electrophoresis confirmed that the isolate obtained from the blood culture (Z5463BC) was identical to Z5463, more precisely to a fourth subculture of this strain used the week before the contamination (Z5463PI). In order to get some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 66 publications
1
47
2
Order By: Relevance
“…These genomic differences can most parsimoniously be explained by 11 mutational events affecting eight different loci, resulting on average in three mutational events per strain pair (95%-CI = [1, 5]). In contrast to a previous case report of a laboratory infection with a mutS deficient mutator strain [18], we could not detect any mutations in mismatch repair genes in any of the four strains pairs. Considering that mutator strains with defects in the mismatch repair pathway display 10–100-fold higher phase variation rates compared to non-mutator strains [66], the number of mutations reported here is therefore in good agreement with the 30 mutations described in the aforementioned work [18].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These genomic differences can most parsimoniously be explained by 11 mutational events affecting eight different loci, resulting on average in three mutational events per strain pair (95%-CI = [1, 5]). In contrast to a previous case report of a laboratory infection with a mutS deficient mutator strain [18], we could not detect any mutations in mismatch repair genes in any of the four strains pairs. Considering that mutator strains with defects in the mismatch repair pathway display 10–100-fold higher phase variation rates compared to non-mutator strains [66], the number of mutations reported here is therefore in good agreement with the 30 mutations described in the aforementioned work [18].…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to a previous case report of a laboratory infection with a mutS deficient mutator strain [18], we could not detect any mutations in mismatch repair genes in any of the four strains pairs. Considering that mutator strains with defects in the mismatch repair pathway display 10–100-fold higher phase variation rates compared to non-mutator strains [66], the number of mutations reported here is therefore in good agreement with the 30 mutations described in the aforementioned work [18]. Together, these 11 mutational events comprised eight SSM and three recombination events due to gene conversion.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This recombination event can cause a hyperpiliated phenotype or, more commonly, a nonpiliated strain, where a frameshift in the pilE sequence creates a premature stop codon (116). A more recent study of isolates recovered from a scientist accidentally infected with a single N. meningitidis strain (302) showed that even with the limited number of in vivo cell divisions (ϳ25) estimated to have occurred before resolution of the infection by antibiotic therapy, at least 7 different pilin variants with different adhesive capacities arose, showing rapid diversification. Neisseria is naturally competent for DNA uptake, in a T4P-dependent manner, and can undergo intergenic recombination with DNA scavenged from its environment.…”
Section: Diversity In Neisseria Pilinsmentioning
confidence: 99%
“…An example of the rapid genetic variation that occurs in N. meningitidis was detailed in a recent report describing the accidental in vivo passage of N. meningitidis in a laboratory worker: an estimated 25 bacterial generations occurred in vivo, resulting in 11 sequence differences between the last passage of the laboratory strain before infection and the blood culture isolate. These genetic changes could affect phenotypes including iron acquisition, adhesion, and lipooligosaccharide structure [23].…”
Section: Genetic Mechanisms That May Contribute To Increased Virulencmentioning
confidence: 99%